Imagery Scripts and a Computerized Subtraction Stress Task Both Induce Stress in Methamphetamine Users: A Controlled Laboratory Study - Garrison, Kathleen J. (Libertas Academica, 2010)
Patients treated for methamphetamine (MA) dependence have a high rate of relapse, and stress is thought to play a key role. We sought to develop a computerized procedure for experimentally inducing stress in MA users. In a within-subjects design, we compared a computerized subtraction stress task (SST) to personalized stress-imagery scripts and a control condition (neutral imagery) in 9 former MA users, recruited in San Francisco in 2006–2007. We assessed blood hormone levels, anxiety and craving for MA on visual analog scales, and the Positive and Negative Affect Schedule and made linear mixed-effects models to analyze the results. Both the SST and stress scripts were effective in inducing self-report markers of stress in MA users. Because the SST is easily reproducible and requires less time of staff and participants, it may be a useful alternative for measuring stress reactivity in drug users.